Hubungan Antara Stres dengan Perilaku Emotional Eating pada Mahasiswa Semester Satu di Purwokerto - Rachma, Haliza Aulia; Ekowati, Wahyu; Kusumawardani, Lita Heni (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2024)
Introduction: First year students in college are prone to experiencing stress because environmental adaptation and new habits while undergoing their first semester lectures. This raises different stress coping for each student. Objectives: This study aims to determine the relationship between stress and emotional eating behavior in first semester students of Health Department in Purwokerto. Methods: The type of research used quantitative research with a cross sectional research design. The sampling technique used purposive sampling with a total of 247 students as respondents. The analysis test in this study used the Rank Spearman test. Results: Respondents experienced moderate category of stress (73.7%) and moderate category of emotional eating (73.7%). The results of the Rank Spearman test between the variables of stres and emotional eating showed p value = 0.000 (p value <0.05). Conclusions: There was a significant relationship between stress and emotional eating in first semester students.